EDUKASI KELUARGA BERENCANA PADA KADER SEBAGAI UPAYA MEWUJUDKAN KELUARGA SEHAT DAN SEJAHTERA DI KECAMATAN KUTA BAHARU KABUPATEN ACEH SINGKIL - Erlina Erlina; Siti Maimunah; Evy Ernawati (LPPM STAI Muhammadiyah Probolinggo, 2026)
Low contraceptive coverage in Kuta Baharu District (40.6%) is largely attributable to knowledge gaps among health cadres who serve as frontline promoters of Family Planning (FP). Structured educational interventions grounded in andragogical principles and visual media are regarded as effective strategies to strengthen cadre capacity. This study aimed to analyze the effect of a FP educational intervention on the knowledge improvement of health cadres in Kuta Baharu District, Aceh Singkil Regency. A pre-experimental one-group pre-test post-test design was employed. All FP cadres within the working area of Kuta Baharu Primary Health Center (n=18) were enrolled via total sampling. The intervention consisted of a 60-minute interactive educational lecture supplemented by a 30-minute discussion session and visual media (PowerPoint and leaflet). A validated 10-item multiple-choice questionnaire (score range 0–100) was used as the measurement instrument. Data were analyzed using descriptive statistics and the Wilcoxon signed-rank test. Mean knowledge scores increased significantly from 72.78 (SD=21.30) at pre-test to 92.78 (SD=7.71) at post-test (Δ=+20.00 points; p<0.001). The proportion of cadres categorized as having Good knowledge (score ≥80) rose from 50.0% to 100.0%. The marked reduction in standard deviation reflected homogenization of understanding across respondents following the intervention. An interactive lecture- and visual media-based FP educational intervention was proven effective in significantly and uniformly improving health cadres’ knowledge. Strengthening cadre capacity through structured education contributes to the optimization of cadres as change agents in FP programs in areas with low contraceptive coverage.